Adebrelimab plus chemotherapy vs. chemotherapy for treatment of extensive-stage small-cell lung cancer from the US and Chinese healthcare sector perspectives: a cost-effectiveness analysis to inform drug pricing - Gan, Yena; Shi, Fenghao; Zhu, He; Han, Sheng; Li, Duoduo (Frontiers in Pharmacology, 2023)
The aim of this study was to evaluate the cost-effectiveness of a recently approved firstline therapy (adebrelimab plus chemotherapy vs chemotherapy alone) for patients with extensivestage small-cell lung cancer (ES-SCLC) in the US and China, and to estimate the reasonable range of adebrelimab price from the decision-makers.Methods: Several partitioned survival models were built to compare the cost and effectiveness of adebrelimab plus chemotherapy vs chemotherapy alone over a 10-year time horizon. Clinical efficacy and safety data were extracted from the CAPSTONE-1 trial. Costs and utilities were obtained from previously published studies. Sensitivity, scenario and subgroup analyses were performed to explore the uncertainty of the model outcomes.